Keefektifan Pengembangan Bahan Ajar Matematika Berbasis Etnomatematika Kelas V SD di Kabupaten Kudus - Sulistiyoningsih Rahayu (IKIP Siliwangi, 2023)
Ethnomathematics-based mathematics teaching materials are a combination of teaching materials that contain cultural elements around the place of residence associated with mathematics subjects. This study aims to: (1) describe the design of the development of mathematics teaching materials based on ethnomathematics class V elementary school; (2) analyze the feasibility of developing mathematics teaching materials based on ethnomathematics class V elementary school; and (3) analyze the effectiveness of the development of mathematics teaching materials based on ethnomathematics class V elementary school. This research is a development research (RnD) model of Borg & Gall. The data source used was 40 grade V students from 3 elementary schools in the Dewi Sartika Cluster, Mejobo District, Kudus Regency. The data collection techniques carried out in this study are test and non-test techniques. Data analysis consists of the feasibility and effectiveness of teaching materials. The results of the research obtained the design of the development of teaching materials starting from analyzing basic competencies and indicators then compiling prototypes of teaching materials. Thenumber of ethnomathematics-based mathematics teaching materials received an average validation of 87% with a very decent category. The effectiveness of teaching materials was carried out by normality test, homogeneity test, and t test. Normality test was tested using posttest value data obtained L0 of 0.1422 and Ltable of 0.190. The homogeneity test results obtained Fcount of 1.0901 witha table F of 2.1683. The t test shows that tcounts 3.2407>ttable 2.02270. Based on these data, it can be concluded that ethnomathematics-based teaching materials are effective in improving the mathematics learning outcomes of grade V elementary school students, the data presentation material.